HOW TO ARCHITECT THE RURAL REGIONS INTO SMART SOCIETY - Al-Sammarraie, Munadil Khaleel Faaeq; Faieq, Alaa K.; Harjan, Sinan A.; Rasheed, Mohammad Maher (European Scientific Journal, ESJ, 2016)
This research explains semantic publishing of information technology awareness in rural areas among electronic government readiness in Republic of Iraq. However, this paper will attempt at reviewing the literature that pertain to this topic in general. At the same time an attempt at reviewing three countries models in India, Brazil, and Taiwan will be made. This is so because, these countries are trying to develop and enhance Electronic Government (EG) project through a publish information system in rural areas of their various countries. This study explains and attempt at proposing a new project in Iraq. The proposal is towards publishing Information Technology (IT) over all governorates in the whole of Iraq. Its main objective is to publish IT in Iraq as a whole. Finally, it aims at decreasing the challenges and issues in different countries with regard to the aforementioned topic. This study will also benefits Iraq by getting to share experiences from other countries. The experiences acquired will help in overcoming the anticipated problems or barriers that may be encountered in the process of applying IT kiosks project in Iraq or any country. At present most developing countries around the world are not using IT kiosk in most of the rural areas, therefore this study is timely.